Les condiments dans les proverbes de Correas : l’huile, le vinaigre et le sel - Eva Galar (Les Cahiers de Framespa)
The experience of our ancestors concerning daily life at home, and more particularly work, health or human relationships, constitutes the raw material of proverbs, material that frequently comes with a symbolic, cultivated burden (translations of Latin phrases or biblical sentences, for instance). On the basis of proverbs collected by Gonzalo Correas in his work Vocabulario de refranes y frases proverbiales (1627), the author has picked out those making mention of three elements that have always been present in Mediterranean homes all throughout history, oil, vinegar and salt, to trace the portrait of popular philosophy and daily life during the Spanish Golden Age. A French translation of all these Spanish proverbs that were widely-used in the seventeenth century is enclosed.